If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 0y + 2z = 24.94 Anything times zero is zero. 4x + 0y + 2z = 24.94 Reorder the terms: 0 + 4x + 2z = 24.94 Remove the zero: 4x + 2z = 24.94 Solving 4x + 2z = 24.94 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2z' to each side of the equation. 4x + 2z + -2z = 24.94 + -2z Combine like terms: 2z + -2z = 0 4x + 0 = 24.94 + -2z 4x = 24.94 + -2z Divide each side by '4'. x = 6.235 + -0.5z Simplifying x = 6.235 + -0.5z
| 11-6x^2-31x= | | 6x+4y+1z=36.39 | | -7+7x-x=-1 | | 13-12d^2-35d= | | 10x+-6=7x+9 | | x=4.2375+-0.5y | | x^2+9x+20.25=-2+20.25 | | 9y+-11=-2 | | 4x+2y=16.95 | | 10+-21=7x | | 1507+20x=1767 | | 6c^3+8c^2-30c= | | 7x-27x=0 | | 1507+20=1767 | | 14=-7x+5x+8 | | 22=6(5-4f) | | 4r+6=16 | | F(z)=z^2-2+2 | | 4x+-15=x | | -12x+48=12x+4 | | 4(2x+3)=2(5x-2)+b | | 12x+48=12x+4 | | 12=2x+4/3-2x/3 | | 2(8-4c)=32 | | a+5=3a | | a=5-3a | | x=4x+6 | | 2(6z+1)-8=78 | | 7m-3-2=(5m-2)+6 | | -6a-18=-2a+2 | | 5n+9=49 | | 0.5x=1.25 |